A survey of opinion: When to start oral anticoagulants in patients with acute ischaemic stroke and atrial fibrillation?. (December 2018) - Munn, David; Abdul-Rahim, Azmil H; Fischer, Urs; Werring, David J; Robinson, Thompson G; Dawson, Jesse
Introduction: There is uncertainty regarding the optimal timing for initiation of oral anticoagulant treatment in patients with recent ischaemic stroke and atrial fibrillation. We surveyed the current UK practice and assessed clinician's opinions of when to use oral anticoagulant in recent stroke patients with atrial fibrillation. Patients and methods: An online survey was sent to stroke physicians within the United Kingdom via their national societies. Results: One hundred and twenty-one clinicians responded to the survey. Ninety-five percent of responders agreed that there was uncertainty regarding timing of oral anticoagulant initiation after atrial fibrillation-related ischaemic stroke. Thirty-six percent of responders followed the '1–3–6–12' European Society of Cardiology guidelines recommendation. Uncertainty was greater in cases of moderate stroke than in cases of transient ischaemic attack (TIA), mild or severe stroke. Eighty-eight percent of responders would be willing to participate in a clinical trial of early versus later initiation of oral anticoagulant after stroke. Direct-acting oral anticoagulants were the preferred oral anticoagulant of choice. Discussion and Conclusion: There is a lack of consensus amongst stroke physicians for when to initiate oral anticoagulant to prevent recurrence in stroke patients with atrial fibrillation. There is little uncertainty regarding TIA. A clinical trial assessing the use of early versus later initiation of direct-acting oral anticoagulant in patients with recent ischaemic stroke and atrial fibrillation would be beneficial.